Utilization of Local History Studies of The Soeracarta Heritage Society Forum as Enrichment in Learning History at Regina Pacis Senior High School in Surakarta - Setyawan, Christianto Dedy; Sariyatun, Sariyatun; Indrawati, Cicilia Dyah Sulistyaningrum (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research was conducted to find out the utilization of local history study of Soeracarta Heritage Society forum in enriching the insight of SMA Regina Pacis Surakarta students. This research used descriptive qualitative method. The data collection techniques applied were interviews and direct observation. Data analysis in this study used interactive model analysis. The results showed that: 1) the identification of local history studies in the history learning process at SMA Regina Pacis Surakarta is still not optimal due to the lack of breadth of insight. 2) the utilization of local history studies of Soeracarta Heritage Society forum is very effective in enriching the insight of SMA Regina Pacis Surakarta students.